Zingiber officinale roscoe and Piper betleextracts enhanced the chemopreventive effect against colon cancer cells by targeting caspase-mediated apoptosis - Yasmin Anum Mohd Yusof,; Shailah Abdullah,; Nur Fatin Nabilah Mohd Sahardi,; Wan Zurinah Wan Ngah,; Suzana Makpol, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Food regimens and herbs have been a target of scientific research in treating cancer. This study aimed to elucidate the effect of Zingiber officinale (ginger) and Piper betle (PB) alone or in combination on the colorectal cancer cell lines HCT116 and HT29. The chemopreventive effect of these extracts was determined by performing cell viability assay, cell cycle analysis, apoptosis analysis, and caspase 3 and 8 activity assays in HCT116 and p53-deficient HT29 cells. Ginger and PB extracts inhibited the proliferation of both cancer cell lines dose-dependently, but the combined extracts inhibited the growth of cancer cells synergistically with an IC50 PB plus ginger < IC50 PB < IC50 ginger. Similarly, the effect of the combined extracts on apoptosis of both cancer cell lines was higher than that of each individual extract. Consistent with the enhancement of caspase activity, both extracts increased the expression of BAX protein, while Bcl-2 protein was decreased. Flow cytometry analysis indicated that the combined extracts arrested a higher percentage of colon cancer cells at the G0/G1 phase with a concomitant decrease in cells in the S phase, indicating that the combined extracts inhibited human colon cancer cell growth by cell cycle arrest at the G0/G1 phase. The inhibitory effect of these combined extracts on cellular proliferation and the induction of apoptosis was synergistic, showing a significant combination index (CI) value < 1.0. The combined extracts of ginger and PB may serve as a potential chemopreventive agent against colon cancer through the induction of caspase-mediated apoptosis.